1977
DOI: 10.1002/j.1537-2197.1977.tb07610.x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Penetration of Naphthaleneacetic Acid: Enhancement by Light and Role of Stomata

Abstract: Light enhanced the penetration of naphthaleneacetic‐1‐14C acid (NAA) into the stomatous lower surface of pear (Pyrus communis L. cv. Bartlett) leaf discs. The light effect was rapidly lost on transfer to the dark and was diminished by pretreatment of leaf discs with a Hill reaction inhibitor (2‐chloro‐4‐ethylamino‐6‐isopropyl‐amino‐s‐triazine). The effect of light on NAA penetration was isolated from its effect on stomatal opening. A similar stimulation of NAA penetration was obtained with stomata opened and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…penetration (Knoche, 1994b;Stevens et al, 1991). These fi ndings are in contrast to earlier studies with most nonionic, agricultural surfactants that did not reduce surface tension suffi ciently to induce stomatal penetration because of the unique morphology (i.e., wall angles) of the stomatal ledges (Green and Bukovac, 1977;Jyung et al, 1965;Schönherr and Bukovac, 1972).…”
Section: Spray Adjuvantsmentioning
confidence: 57%
“…penetration (Knoche, 1994b;Stevens et al, 1991). These fi ndings are in contrast to earlier studies with most nonionic, agricultural surfactants that did not reduce surface tension suffi ciently to induce stomatal penetration because of the unique morphology (i.e., wall angles) of the stomatal ledges (Green and Bukovac, 1977;Jyung et al, 1965;Schönherr and Bukovac, 1972).…”
Section: Spray Adjuvantsmentioning
confidence: 57%
“…Ions like Ag + , forming visible black deposits after precipitation in the apoplast or the cytoplasm after having penetrated the cuticle, form good indicators for the localization of polar paths of diffusion within cuticles (Lord et al, 1979). This has already been shown in a series of experiments, in which it was observed that the cuticle covering stomatal cells obviously has a higher permeability to polar, ionized salts, like silver nitrate (Franke, 1964;Green and Bukovac, 1977;Schlegel and Schönherr, 2002). By this approach with Vicia faba leaves, it is evident that, in addition to the stomata, glandular trichomes themselves and the base of these trichomes can be identified as sites of polar paths of diffusion (Fig.…”
Section: T H E P O L a R P A T H O F D I F F U S I O Nmentioning
confidence: 76%
“…Entry of the treatment solution through the stomatal pore seems unlikely under such conditions. Guard cells have been implicated as preferential absorption sites (9,15,31). Ectoteichodes (ectodesmata) are especially plentiful in walls and areas above guard cells (8,10).…”
Section: Methodsmentioning
confidence: 99%